2021
DOI: 10.3390/ma14164767
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Formwork Pressure for Self-Compacting Concrete—A Review of Prediction Models and Monitoring Technologies

Abstract: The maximum amount of lateral formwork pressure exerted by self-compacting concrete is essential to design a technically correct, cost-effective, safe, and robust formwork. A common practice of designing formwork is primarily based on using the hydrostatic pressure. However, several studies have proven that the maximum pressure is lower, thus potentially enabling a reduction in the cost of formwork by, for example, optimizing the casting rate. This article reviews the current knowledge regarding formwork press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Fresh concrete density, as a main parameter in hydrostatic pressure, has been identified in previous studies as a parameter that significantly affects form pressure. This was specifically addressed by [ 7 , 12 ]. Air temperature was also identified by [ 1 ] as a parameter that significantly affects form pressure over time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fresh concrete density, as a main parameter in hydrostatic pressure, has been identified in previous studies as a parameter that significantly affects form pressure. This was specifically addressed by [ 7 , 12 ]. Air temperature was also identified by [ 1 ] as a parameter that significantly affects form pressure over time.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that form pressure is affected by several parameters, and these parameters are generally classified into parameters related to mixture design and material properties, the fresh concrete properties of the mix, and the placement method and speed of casting [ 12 ]. However, the degree of impact of these parameters is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The bulging effect on the bottom half of the modules can be explained by the fact that the greater the quantity of concrete is poured, the more the inside pressure of the formwork increases, exposing the mould's structure to additional deformations (Gamil et al 2021;Ovarlez and Roussel 2006).…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…When casting concrete, several properties are needed to judge the quality and applicability of concrete such as slump for normal concrete, slump flow for Selfcompacting concrete (SCC), T500 for SCC, density, air content, yield stresses, concrete temperature, ambient temperature, and viscosity. These parameters are needed for specific equipment and expertise (Gamil et al, 2021;Gamil et al, 2023). It comes with the need for machine learning to substitute manual testing using historical databases owned by corporate or research institutions.…”
Section: Fresh Concrete Propertiesmentioning
confidence: 99%